A Review of Laboratory Studies on Use of Low Density Polyethene (LDPE) and Non-Silica as Bitumen Modifiers (International Journal of Innovative Research in Computer Science & Technology, 2022)
Pavements experience numerous distresses  including rutting, fatigue cracking, ravelling, etc. as a result  of rising axle loads, rising traffic volumes, and poor  maintenance. These annoyances lengthen travel times and  raise maintenance costs for automobiles while lowering the  pavement's riding quality. By incorporating various  additives like polymers, nanomaterials, and other  compounds into bitumen, one can improve the desirable  qualities of the bitumen binder and so lessen the likelihood  of these distresses occurring. Although they have demonstrated beneficial benefits on bitumen, polymer  additives including polyethylene, ethylene-butyl acrylate  (EBA), and styrene-butadiene-styrene (SBS) have certain  downsides, such as low storage stability[2]. More study is  currently being done to determine how utilising  nanoparticles can improve the performance of pavements.  Nanomaterials are advantageous because they have a lot of  surface area and good dispersion.
Keywords: Nano-Materials; LDPE (Low Density Polyethylene); Softening Point; Penetration Value